Influence of mesoscale friction interface geometry on the nonlinear dynamic response of large assembled structures - Yuan, Jie; Salles, Loic; Nowell, David; Schwingshackl, Christoph (Mechanical systems and signal processing, 2023)
Friction interfaces are unavoidable components of large engineering assemblies since they enable complex designs, ensure alignment, and enable the transfer of mechanical loads between the components. Unfortunately, they are also a major source of nonlinearities and uncertainty in the static and dynamic response of the assembly, due to the complex frictional physics occurring at the interface. One major contributor to the nonlinear dynamic behavior of the interface is the mesoscale geometry of a friction interface. Currently, the effects of the interface geometry on the nonlinear dynamic response is often ignored in the analysis due to the high computational cost of discretizing the interface to such fine levels for classical finite element analysis. In this paper, the influence of mesoscale frictional interface geometries on the nonlinear dynamic response is investigated through an efficient multi-scale modeling framework based on the boundary element method. A highly integrated refined contact analysis, static analysis, and nonlinear modal analysis approach are presented to solve a multi-scale problem where mesoscale frictional interfaces are embedded into the macroscale finite element model. The efficiency of the framework is demonstrated and validated against an existing dovetail dogbone test rig. Finally, the effects of different mesoscale interface geometries such as surface waviness and edge radius, are numerically investigated, further highlighting the influence of mesoscale interface geometries on the nonlinear dynamics of jointed structures and opening a new research direction for the design of friction interfaces in friction involved mechanical systems. •Proposed a highly efficient multi-scale modelling framework to evaluate the influence of friction interfaces in the dynamical response of large assembled structures.•Successfully integrated adaptive reduced order modeling and nonlinear modal analysis into the multi-scale modelling framework.•Investigate the effects of mesoscale friction interface on the nonlinear dynamical response for the first time.•Successfully performed mesoscale interface geometrical study using a high fidelity aero-engine fan blade dovetail test rig model.•The effects of different mesoscale interface geometries such as surface waviness and edge radius are numerically investigated.